IMPROVING THE STUDENTS’ SPEAKING ABILITY THROUGH ROTATING TRIO EXCHANGE STRATEGY - Maharida Maharida (Universitas Muhammadiyah Makassar, 2015)
This research purposed to find out how the improvement of the students’ speaking accuracy and fluency through Rotating Trio Exchange Strategy at the eighth year of SMPN 1 Pallangga. This research was a classroom action research (C.A.R) which consisted of two cycles in which every cycle consisted of four meetings. The subject of this research was one of the classes with the total of students is 33 students. The instruments were oral test and observation sheet. The research findings of this research indicated the students’speaking ability in terms of accuracy and fluency through Rotating Trio Exchange Strategy was effective and significant in improving the students’ speaking ability. It was proved that the findings indicate that the mean score of cycle II was greater than the mean score of cycle I (7.55 5.84) and the mean score of cycle I also was greater than the mean score of D-test (5.84 4.19), it means that Rotating Trio Exchange Strategy improved the students’ speaking ability in English. Besides, it is better to use in teaching speaking ability than the conventional strategies because this was also improved the students' interest to make them active in learning the speaking ability. The conclusion of the research, Rotating Trio Exchange Strategy improved the student improved the student ability in accuracy and fluency.